Evaluation of neutrophil-to-lymphocyte ratio and immune response in patients vaccinated with Pfizer-Biontech vaccine - Ridvana Mediu; Ariol Rama; Edmond Puca (Journal of Infection in Developing Countries)
Introduction: Research on SARS-CoV-2 virus has focused on aspects such as treatment, virology, epidemiology and vaccine development. The efficacy of vaccines against SARS-CoV-2 is important for controlling the pandemic. This study assessed how the immune response is affected by age and gender, and its role in causing inflammation as measured by neutrophil-to-lymphocyte ratio (NLR) in vaccinated patients versus non-vaccinated COVID-19 negative patients.